Narcotic Use and Prevention Measures in the Rokan Hilir Legal Jurisdiction - Jenius Pardede, Rianto; Abidin Pakpahan, Zainal; Siahaan, Nimrot (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to identify the factors that influence the occurrence of narcotics abuse in the Rokan Hilir Legal Area and analyze the efforts made by the Rokan Hilir Police and BNNK in preventing narcotics abuse in the region. The research method used is a combination of Normative and Empirical Legal research. The results showed that the factors influencing drug abuse in the Rokan Hilir jurisdiction include trial and error due to curiosity, lack of self-confidence, economic factors, lack of understanding of the dangers of drug abuse, and the influence of lifestyle. In addition, efforts made by the Rokan Hilir Police, together with BNNK, to prevent drug abuse in the region consist of promotive, preventive, and repressive efforts. The implication of this research is the importance of increasing public understanding of the dangers of narcotics abuse as well as expanding and increasing the effectiveness of preventive and repressive efforts carried out by the authorities in order to reduce the number of narcotics abuses in the Rokan Hilir jurisdiction.